Ethnic cleansing in the Balkans : nationalism and the destruction of tradition - Carmichael, Cathie (Routledge advances in European politics, 2002)
"This book looks at the phenomenon of ethnic cleansing in the Balkans over the last two hundred years. It argues that the events of the last two centuries can be demystified, that the South East of Europe was not destined to become violent and that construction of the Balkans as endemically violent misses an important political point and historical point."--BOOK JACKET.